Pendidikan Islam Prespektif Imam Al-Ghazali dalam Meningkatkan Nilai Moral Anak - Eny Fatimatuszuhro Pahlawati (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2020)
This study aims to describe the Islamic education from the perspective of Imam Al-Ghazali in improving children's moral value. This type of research is a library research with a qualitative descriptive approach. The data collection technique uses documentation techniques, in the form of books, literature, journals, and written documents in both print and electronic media. While the data analysis technique uses content analysis techniques (content analysis). The results show that the concept of Islamic Education According to Al-Ghazali is actually based on his thoughts on humans whose nature will not change, so that the concept is always actual and never obsolete, and is able to answer the challenges facing the world of education today. In actualizing Islamic education in enhancing children's moral values, Al-Ghazali sparked a special method of Moral education, the exemplary method is the method most prioritized by Al-Ghazali to increase children's moral values.